Studi Deskriptif Karakter Lagu Anak Pada Buku Tematik Siswa Sekolah Dasar Kelas II Tema 5 Muatan SBdP - Dera Leoni; Pebrian Tarmizi; Bambang Parmadie (JURIDIKDAS, 2021)
AbstractThis study aimed to describe lyrics and tempo characters in kids’ songs on 5th theme thematic book containing cultural arts and crafts material of 2nd grade elementary students. This study was a library qualitative study which was a text study with kids’ songs on 5th theme thematic book containing cultural arts and crafts material of 2nd grade elementary students as the subject. In a thematic book entitled my experience, there were 6 songs including Pelangi-pelangi, Burung Tantina, Kebunku, Kunang-kunang, Cemara, and Kupu-kupu. The main instrument in this study was the researcher herself, meanwhile the supporting instruments were observation and documentation study. The data collecting techniques were observation technique to observe kids’ songs on the book and documentation study including the 5th theme thematic book of 2nd grade elementary students and music sheets (music notations). The data analysis technique in this study was taxonomy analysis technique. The results showed that there were five of six songs which had happy lyrics character and there was one song which had sad lyrics character. The tempo characters of the six songs were rather fast tempo (Allegreto) for one song, moderate tempo (moderato) for two songs, normal walking moderate tempo (Andante) for two songs, and very slow tempo (Lento) for one song. Hence, from the six kids’ songs, the most lyrics character found was happy character and the most tempo character found was moderate tempo with different types which were two songs having moderato tempo and two songs having andante tempo.Keywords: Kid’s Songs, Character, Tempo, Lyrics, Cultural Arts, Crafts